Investigation of thermal performance of phase change material in a rotating shell-and-tube heat exchanger - Kiyak, Burak (Elsevier, 2025)
This study presents a three-dimensional (3D) numerical investigation of the thermal performance of phase change material (PCM) in a rotating shell-and-tube latent heat thermal energy storage (LHTES) system. The analysis employs the finite volume method (FVM) to examine various rotational cases (stationary, 180 degrees, 360 degrees, and 720 degrees) and inclination angles (theta = 0 degrees, 22.5 degrees, and 45 degrees) at heat transfer fluid (HTF) temperatures of T = 40 degrees C and 50 degrees C, assessing their impact on heat transfer efficiency and energy storage capabilities. The primary motivation behind this study is to address the low thermal conductivity of PCMs, which limits their heat transfer efficiency in storage applications. In contrast to previous studies that primarily concentrated on rotating the heat transfer fluid (HTF) tube or employing passive enhancement techniques such as fins or porous media, the present work proposes a novel approach by implementing angular rotation of the entire LHTES unit. This method provides an alternative enhancement strategy that mitigates common limitations associated with conventional methods, including increased structural complexity, additional mass, and reduction in the effective PCM storage volume. The results indicate that higher rotational speeds significantly accelerate the melting process, with the rotational effect being especially pronounced at lower HTF inlet temperatures. Specifically, a 720 degrees rotation resulted in a reduction in melting time ranging from 24.2 % to 61.5 % compared to the stationary case. In addition, the rotational movement provides a more uniform temperature distribution within the PCM, leading to improved energy storage efficiency. These findings underscore the potential of rotational motion as an effective method for optimizing PCM-based thermal energy storage systems.
Keywords: Phase change material; Shell and tube; LHTES; Heat exchanger; Rotation; Thermal performance; Numerical simulation